An optimized protocol using Steedman's wax for high-sensitivity RNA in situ hybridization in shoot apical meristems and flower buds of cucumber - Cui WANG; Jin-jing SUN; Xue-yong YANG; Li WAN; Zhong-hua ZHANG; Hui-min ZHANG (Journal of Integrative Agriculture, 2023)
In situ mRNA hybridization (ISH) is a powerful tool for examining the spatiotemporal expression of genes in shoot apical meristems and flower buds of cucumber. The most common ISH protocol uses paraffin wax; however, embedding tissue in paraffin wax can take a long time and might result in RNA degradation and decreased signals. Here, we developed an optimized protocol to simplify the process and improve RNA sensitivity. We combined embedding tissue in low melting-point Steedman's wax with processing tissue sections in solution, as in the whole-mount ISH method in the optimized protocol. Using the optimized protocol, we examined the expression patterns of the CLAVATA3 (CLV3) and WUSCHEL (WUS) genes in shoot apical meristems and floral meristems of Cucumis sativus (cucumber) and Arabidopsis thaliana (Arabidopsis). The optimized protocol saved 4–5 days of experimental period compared with the standard ISH protocol using paraffin wax. Moreover, the optimized protocol achieved high signal sensitivity. The optimized protocol was successful for both cucumber and Arabidopsis, which indicates it might have general applicability to most plants.